Socio-economic factors to influence international success of Soviet national ice hockey team in the 70s of XX century - Titovsky, A. V.; Vyprikov, D. V.; Goryunova, O. B. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to find the socio-economic factors for influence on the Soviet national ice hockey team successes on the global arenas in 1970-1979.